The slave dancer : a novel - Fox, Paula (Atheneum Books for Young Readers, 2001)
One day, thirteen-year-old Jessie Bollier is earning pennies playing his fife on the docks of New Orleans; the next, he is kidnapped and thrown aboard a slave ship, where his job is to provide music while shackled slaves "dance" to keep their muscles strong and their bodies profitable. As the endless voyage continues, Jessie grows increasingly sickened by the greed, brutality, and inhumanity of the slave trade, but nothing prepares him for the ultimate horror he will witness before his nightmare ends--a horror that will change his life forever.